Faktor-faktor Yang Mempengaruhi Minat Berwirausaha Mahasiswa - Ardyanti Nilasari Saputri; Indira Januarti (Ikatan Sarjana Ekonomi Indonesia Cabang Semarang, 2020)
This study aims to analyze the influence of internal factors and external factors on the interest of student entrepreneurship. The sample of this study was 100 students from the Faculty of Economics and Business, Diponegoro University. Hypothesis testing uses multiple regression analysis.. The results of this study indicate the need for achievement, family and social environment has a significant positive effect on the interest of student entrepreneurship. While innovation, personal control, and self-esteem do not affect the interest of student entrepreneurship.